The effects of drugs on Onchocerca volvulus: 1. Methods of assessment, population dynamics of the parasite and the effects of diethylcarbamazine - Duke, B. O. L. (1968)
It is important to standardize quantitative methods for assessing the action of drugs on Onchocerca volvulus in man. There are certain disadvantages to making observations on adult worms removed from excised nodules in treated patients, but a great deal of information on drug action can be obtained by making a careful study of the concentrations of microfilariae in multiple weighed skin snips taken before treatment and at intervals after treatment. Before drug trials can be carried out intelligently by this method it is necessary to know the normal length of life of the various stages of the parasite in man. By a variety of experimental methods the life-spans of the adult worms and the microfilariae have been determined, as well as the duration of the prepatent interval. Diethylcarbamazine can be used at doses that are effectively microfilaricidal but have no action on the adult worms. This drug can therefore be used to eliminate any residual microfilariae that remain after treatment with a new drug under trial, thus permitting a more rapid assessment of the latter's action on adult worms.